A comparative study looking at trauma and orthopaedic operating efficiency in the COVID-19 era - Mercer, Scott Thomas (Perioper Care Oper Room Manag, 2020)
BACKGROUD: COVID-19 has led to a reduction in operating efficiency. We aim to identify these inefficiencies and possible solutions as we begin to pursue a move to planned surgical care. METHODS: All trauma and orthopaedic emergency surgery were analysed for May 2019 and May 2020. Timing data was collated to look at the following: anaesthetic preparation time, anaesthetic time, surgical preparation time, surgical time, transfer to recovery time and turnaround time. Data for 2019 was collected retrospectively and data for 2020 was collected prospectively. RESULTS: A total of 222 patients underwent emergency orthopaedic surgery in May 2019 and 161 in May 2020. A statistically significant increase in all timings was demonstrated in 2020 apart from anaesthetic time which demonstrated a significant decrease. A subgroup analysis for hip fractures demonstrated a similar result. No increase in surgical time was observed in hand and wrist surgery or for debridement and washouts. Although the decrease in anaesthetic time is difficult to explain, this could be attributed to a reduction in combined anaesthetic techniques and possibly the effect of fear. The other increases in time demonstrated can largely be attributed to the PPE required for aerosol generating procedures and other measures taken to reduce spread of the virus. These procedures currently form a large amount of the orthopaedic case load. CONCLUSION: COVID-19 has led to significant reductions in operating room efficiency. This will have significant impact on waiting times. Increasing frequency of regional anaesthesia concurrently with non-aerosol generating surgeries may improve efficiency.